Chronic His bundle block. Clinical, electrocardiographic, electrophysiological, and follow-up studies on 16 patients. Issue 12 (December 1976) - Gupta, P K; Lichstein, E; Chadda, K D
Abstract : This report describes 16 patients with block within the His bundle seen over a period of 55 months. Ten were women and 6 men, with an average age of 76 years, range, 42 to 98 years. All patients had His bundle recordings showing split His bundle potentials (H and H) (13 patients) or narrow QRS with block distal to the His bundle potential (3 patients). Of the 16 patients, 10 had complete heart block, 4 second degree AV block (2 patients with Mobitz type II, and 2 with 2:1), and 2 first degree AV block. Ten patients had a narrow QRS in the conducted beats or escape rhythms. Intravenous atropine (1 to 2 mg) had a variable effect on AV conduction and the rate of the escape rhythm. Twelve patients have had a permanent pacemaker implanted. During the follow-up period, 10 patients died 1 to 31 months from the time of initial examination. The remaining 6 patients (5 with pacemaker) are alive 3 to 58 months later.